Conciencia ambiental y manejo de residuos sólidos en alumnos de secundaria del Colegio Fe y Alegría el Milagro, Loreto, 2024 - Huiñapi Canaquiri, Waxter (2025)
This study addresses environmental awareness and solid waste management among students at Fe y Alegría El Milagro School, aiming to identify the level of environmental awareness and waste management practices within the school environment. The theoretical framework is based on the need to promote pro environmental behaviors and proper waste management, with an emphasis on education as a tool for sustainability. The methodology employed was a quantitative approach, using surveys to assess students' knowledge and attitudes towards the environment and solid waste management. The results show favorable environmental awareness, especially regarding nature protection and recycling, although gaps remain in knowledge about current environmental issues and individual responsibility for reducing the ecological footprint. Additionally, it was observed that women exhibit higher awareness and waste management practices compared to men. It is concluded that environmental education needs to be strengthened from the early grades and sustainable practices such as composting should be promoted.